Focus Group Discussion on Youth Participation in Vertical Housing Neighbourhood Space / Kamarul Ariff Omar … [et.al.] - Omar, Kamarul Ariff; Omar, Dasimah; Othman, Saberi; Mohd Yusoff, Zaharah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Focus group discussion series were set up at the vertical housing of Kerinchi People Housing Project, Lembah Pantai with two different groups in separate venue and time. The analysis was done by using Atlas.ti after transcribing and coding the audio-taped of discussion, searching for networking on youth participation. The findings show youth demandingly indoor space compared to outdoor space due to open space inadequacy and absence of space quality yet lost the sense of belonging. Furthermore, the residents' committee neglected youth participation in the decision-making process or meeting with the committee has resulted youth for not to participate in the community actively.